Mitos Wacana Pendidikan Karakter Perempuan Minangkabau: Studi Kasus Kabupaten Padang Pariaman - Muhammad Yunis (Politeknik Negeri Padang, 2014)
This study titled 'Myth For Women Character Education Discourse of Minangkabau; Case Study of PadangPariaman '' is one of the studies that tried to reformulate the old wisdom and knowledge that is useful for the creation of models tolearning and character education of young generation in the future, especially women. In the formulation of this model, the authorsuse qualitative methods ethnometodology approach in the collection and analysis of data, with the hope of purity assessment ismaintained.The data can be by way of participation and interview.The processing and data analysis, deconstruction required readings. Deconstruction is not just unload but re-downloaddestructs. (evaluation) with the help of linguistics that speech acts (elaboration) and semiotics (significance). The way it works, thedata that has been collected will enter the stage of processing; grouping based on the research objectives; analyzed by speech acttheory; pared with the theory of semiotics; and to formulate a model of learning as a result of the evaluation.